Relationship between Physical Activity and Physical Fitness in Preschool Children: A Cross-Sectional Study. (21st November 2017) - Fang, Hui; Quan, Minghui; Zhou, Tang; Sun, Shunli; Zhang, Jiayi; Zhang, Hanbin; Cao, Zhenbo; Zhao, Guanggao; Wang, Ru; Chen, Peijie
Abstract : Purpose . To evaluate the relationships between objectively measured physical activity and physical fitness among preschool children. Methods . A total of 346 participants (201 boys and 145 girls) aged 3.5–5.5 years (M = 4.5 yr, SD = 0.47) from Shanghai, China, completed physical fitness assessments, including triceps skinfold thickness (TSFT), grip strength, tennis throwing, sit and reach test, standing long jump, balance beam, 10mSRT, and 20mSRT. Physical activity was objectively measured by ActiGraphGT3X+ accelerometer. Multiple linear regression models were used to explore the cross-sectional associations between PA and physical fitness after adjusting for age, gender, BMI, and valid wearing time. Results . Positive associations were observed between stand long jump (p < . 01 ), tennis throwing (p < . 01 ), laps in 20mSRT (p < . 01 ), and MVPA. However, TSFT (p < . 05 ), time in 10mSRT (p < . 01 ), and balance beam (p < . 05 ) were negatively associated with MVPA. Furthermore, positive associations were found between stand long jump (p < . 01 ), tennis throwing (p < . 01 ), and MVPA only in boys. Negative associations were found between time on balance beam (p < . 0 1 ) and MVPA only in girls. Conclusions . MVPA appears to be an effective and reliable predictor of preschoolers' physical fitness. Boys' body composition, muscular strength, explosive strength, agility, aerobic fitness, girls' agility, aerobic fitness, and balance could improve as MVPA increases.